Latent tuberculosis infection treatment completion in Biscay: differences between regimens and monitoring approaches - Ortiz Laza, N.; Lopez Aranaga, I.; Toral Andres, J.; Toja Uriarte, B.; Santos Zorrozua, B.; Altube Urrengoechea, L.; Garros Garay, J.; Tabernero Huguet, E. (Frontiers in Medicine, 2023)
Introduction Contact tracing and treatment of latent tuberculosis infection (LTBI) is a key element of tuberculosis (TB) control in low TB incidence countries. A TB control and prevention program has been active in the Basque Country since 2003, including the development of the nurse case manager role and a unified electronic record. Three World Health Organization-approved LTBI regimens have been used: isoniazid for 6 months (6H), rifampicin for 4 months (4R), and isoniazid and rifampicin for 3 months (3HR). Centralized follow-up by a TB nurse case manager started in January 2016, with regular telephone follow-up, telemonitoring of blood test results, and monitoring of adherence by electronic review of drugs dispensed in pharmacies. Objective To estimate LTBI treatment completion and toxicity of different preventive treatment regimens in a real-world setting. Secondary objective: to investigate the adherence to different approaches to preventive treatment monitoring. Methods A multicentre retrospective cohort study was conducted using data collected prospectively on contacts of patients with TB in five hospitals in Biscay from 2003 to 2022. Results A total of 3,066 contacts with LTBI were included. The overall completion rate was 66.8%; 86.5% of patients on 3HR (n = 699) completed treatment vs. 68.3% (n = 1,260) of those on 6H (p < 0.0001). The rate of toxicity was 3.8%, without significant differences between the regimens. A total of 394 contacts were monitored by a TB nurse case manager. In these patients, the completion rate was 85% vs. 67% in those under standard care (p < 0.001). A multivariate logistic regression model identified three independent factors associated with treatment completion: being female, the 3HR regimen, and nurse telemonitoring. Conclusion 3HR was well tolerated and associated with a higher rate of treatment completion. Patients with nurse telemonitoring follow-up had better completion rates.